The carbon source-sink function of Hulun Lake, a large shallow eutrophic lake in northern China - Zhang, Fengju; Xue, Bin; Yao, Shuchun (Frontiers in Ecology and Evolution, 2025)
Lakes are known to play a crucial role in the world-wide carbon cycling due to the efficient organic carbon burial as well as large amount of CO2 emissions to the atmosphere. Despite the increasing importance of understanding these processes in the context of global warming and escalating human activities, the carbon source-sink dynamics of lakes remain elusive. In this study, we compared two approaches, a mass balance approach and the CO2 emission-carbon burial balance method to investigate the role of lake as carbon source or sink in Hulun Lake (the largest lake in northeastern China) from June 2015 to May 2016. Both approaches converged on the same conclusion that Hulun Lake was a great carbon source. With the overall mass balance calculations, total carbon input was 112.4×103 t during our study period, with the largest input was from the inlet rivers (107.5×103 t). The total carbon output was 448.2×103 t, and the CO2 emission accounted for about 99% of the output. The net carbon budget was -289×103 t, suggesting that Hulun Lake was a great carbon source. Furthermore, the total C-CO2 emission was three times higher than sediment carbon accumulation, stressing Hulun Lake was an important carbon source. The carbon source function mainly results from low primary production, long lake water residence time, high allochthonous carbon inputs (carbon derived from external terrestrial and atmospheric sources) and intensive human activities (e.g., grazing intensity up to 2.0 livestock units/ha, approaching the maximum stocking rate for Inner Mongolian grasslands). While further research is necessary to generalize these findings, our results provide compelling evidence for the significant role of lakes in the carbon cycle, and highlighting the importance of considering both carbon burial and carbon emission in assessments of the carbon sink-source function.